LEMBAR KERJA MAHASISWA TERINTEGRASI MODEL GUIDED INTERACTION IN TEAM (GIT) UNTUK PENDIDIKAN LINGKUNGAN HIDUP - Ichsan, Ilmi Zajuli; Winarti, Euis; Pertiwi, Santhi; Alibowo, Sugi; Ilyasa, Feryl; Yuliana, Eva (FKIP Universitas Tanjungpura, 2025)
Environmental education implemented at the tertiary level often impacts changes in student behavior. This makes the development of environmental education at the tertiary level important to be carried out sustainably. The purpose of this study was to develop a student worksheet integrated with the Guided Interaction in Team (GIT) model. The method used in this study was research and development (R&D). The results of this study indicate that the student worksheet integrated with the GIT model has a very valid category with a percentage of expert I scores of 90% and a percentage of expert II scores of 87.50%, making it suitable for use in learning. The results of this study confirm that learning innovations need to be continuously developed better so that environmental education can run properly. The conclusion of this study is that the developed student worksheet is valid for use in classroom learning. Suggestions for further research are to develop other learning models that are more integrated with learning tools.